On the effective and automatic enumeration of polynomial permutation classes. (September 2016) - Homberger, Cheyne; Vatter, Vincent
Abstract: We describe an algorithm, implemented in Python, which can enumerate any permutation class with polynomial enumeration from a structural description of the class. In particular, this allows us to find formulas for the number of permutations of length n which can be obtained by a finite number of block sorting operations (e.g., reversals, block transpositions, cut-and-paste moves).